"A shared energy": West African drumming fosters cross-cultural understandings in Australia. Issue 1 (2nd January 2022) - Joseph, Dawn
ABSTRACT: This study builds on and contributes to work in the area of African music in Australia in community settings. This research explores why people came together to share music-making and practice at a drumming retreat, and what they experienced as a recreational group music activity. Employing thematic analysis to code the data, two overarching themes (drumming for leisure and cultural connections) are discussed. I argue that West African drumming as a "shared energy" experience has the power to positively impact participants' lives, fostering cross-cultural understandings. Exploring another culture helps to dispel myths and encourages discussion that may promote cultural diversity and respect in a multicultural Australia.